Discovery of chiral dihydropyridopyrimidinones as potent, selective and orally bioavailable inhibitors of AKT. Issue 10 (1st June 2018) - Parthasarathy, Saravanan; Henry, Kenneth; Pei, Huaxing; Clayton, Josh; Rempala, Mark; Johns, Deidre; De Frutos, Oscar; Garcia, Pablo; Mateos, Carlos; Pleite, Sehila; Wang, Yong; Stout, Stephanie; et al.
Graphical abstract: Highlights: Chiral DHP as hinge binder provided high AKT1 selectivity over ROCK2/AGC kinases. Emphasis on physicochemical properties over potency led to developable compounds. Reducing the HB acceptor strength of compounds with high P-gp efflux improved Ppass. Abstract: During the course of our research efforts to develop potent and selective AKT inhibitors, we discovered enatiomerically pure substituted dihydropyridopyrimidinones (DHP) as potent inhibitors of protein kinase B/AKT with excellent selectivity against ROCK2 . A key challenge in this program was the poor physicochemical properties of the initial lead compound 5 . Integration of structure-based drug design and physical properties-based design resulted in replacement of a highly hydrophobic poly fluorinated aryl ring by a simple trifluoromethyl that led to identification of compound 6 with much improved physicochemical properties. Subsequent SAR studies led to the synthesis of new pyran analog 7 with improved cell potency. Further optimization of pharmacokintetics properties by increasing permeability with appropriate fluorinated alkyl led to compound 8 as a potent, selective AKT inhibitors that blocks the phosphorylation of GSK3β in vivo and had robust, dose and concentration dependent efficacy in the U87MG tumor xenograft model.